Study on the characteristics and influencing factors of suspended sediment front in the eastern Qiongzhou Strait - Liu Jie (E3S Web of Conferences)
The eastern shoal of the Qiongzhou Strait is considered a crucial potential sand resource, and its sediment dynamics are of great interest for both environmental and economic reasons. To better understand these dynamics, this study employed the ROMS (Regional Ocean Modeling System) ocean model to simulate suspended sediment transport during the winter and summer of 2019. The model incorporated a variety of environmental factors, including wave conditions, tidal forces, currents, temperature, and salinity, to capture the complex interactions affecting sediment movement. The simulation results revealed significant seasonal variations in sediment transport patterns and the shape of sediment fronts. During the winter months, sediment primarily moves eastward, with increased sediment concentration observed near the eastern shoal. This results in the pushing of the sediment front further offshore. Conversely, in the summer, the sediment transport pattern reverses, with sediment moving in the opposite direction. Wind waves, especially near the eastern Leizhou Peninsula and the Qiongzhou Strait, play a crucial role in influencing sediment movement, particularly near the shoal. These findings highlight the complex interplay of seasonal factors in shaping sediment dynamics in this region.